Implementation Of Integrative Legal Theory And Project Management Approach In Dispute Resolution Through Arbitration In International Commercial Contracts - Rahmadini, Verny; Nurlaily, Nurlaily; Syarief, Elza (Universitas Internasional Batam, 2025)
This study examines the integration of arbitration mechanisms and project management in resolving international trade disputes. Arbitration is chosen as the preferred dispute resolution method due to its confidential, flexible, final, and binding nature, as well as the international enforceability of its awards. In contrast, resolving international commercial contract disputes through Indonesian courts has proven to be time-consuming, involving multiple layers of appeal, and resulting in judgments that are difficult to enforce across jurisdictions. This normative juridical research employs primary and secondary legal materials to analyze legal issues and managerial approaches within arbitration. Romli Atmasasmita’s Integrative Legal Theory is used to bridge the values of legal certainty, utility, and justice, while project management concepts are applied to structure arbitration proceedings as a project consisting of planning, execution, and closing phases. The findings indicate that arbitration procedures align with the project life cycle, enabling dispute resolution to be carried out more effectively and systematically. The integration of these two approaches is evident in international commercial contracts, where arbitration clauses are commonly included as the designated dispute resolution mechanism.